Exploration and Estimation of Gravel Resource Potential in Southeast Chukchi Sea Continental Shelf Off Kivalina, Alaska - S. Naidu; J. Kelley; Roger Amato (International Marine Minerals Society)
The Alaskan Continental Shelf covers 76 % of the total shelf area of the United States. There are a lot of potential gravel deposits in the Alaskan offshore region. The gravel resources are currently not feasible for mining for the following reasons (U.S Congress, 1987): 1. Much of the glacial gravel is poorly sorted. 2. Gravel deposits are overlain by sandy and muddy layers. With the sea level expected to rise 70 cm in the next 100 years (Intergovernmental Panel on Climate Change, IPCC, 2001; Day, 2004), erosion of coastlines will be a major problem not only in Alaska but worldwide. Hence beach nourishment projects designed to minimize erosion will require large volumes of sand and gravel. Offshore areas will become a logical source for the fill material because of their proximity and ready availability. It is likely that future supply of coarse aggregate in Alaska may involve exploitation of marine deposits. The Chukchi Sea is a potentially favorable region for this type of mining because of extensive deposits of paleo beach and other relict gravel found in the near shore region (Stauffer, 1987). However a systematic analysis of potential gravel resource has not yet been conducted and it is the purpose of this research to estimate the size, extent and variability of gravel material that may be available in the continental shelf, offshore Kivalina.